Exploring the effects of perceived justice and motivation on student satisfaction regarding entrance exams for higher education - BAO, Nguyen Van (KDI School, 2021)
For many Vietnamese students, the national high school graduation examination is one of the most important exams in their lives, transitioning from upper-secondary education to tertiary education. While the importance of the exam is significant in the country where a degree is inevitable for a stable job in the future, policies on the national examination have significantly changed since 2015. By using the concept of justice and motivation, the current study aimed to explore the effects of justice dimensions and motivation on student satisfaction in the context of education, specifically focusing on the national examination for higher education. In this regard, this study proposed a conceptual model and conducted an online survey to test relevant hypotheses. The empirical findings of the study found that procedural, distributive justice, and intrinsic motivation affected the level of student satisfaction. More broadly, these results would be useful for policymakers to make more informed choices and also suggest further programs and projects of the Vietnamese government, aiming to develop the system of university admissions in the future.
Thesis(Master) -- KDI School: Master of Development Policy, 2021
Keywords: High school students--Vietnam; Education, Higher